PENGARUH ONLINE CUSTOMER REVIEW TERHADAP KEPERCAYAAN MAHASISWA PENGGUNA SHOPEE DI FAKULTAS EKONOMI BISNIS UNIVERSITAS NEGERI MAKASSAR - Dilla Apriliana Mahrun; Muhammad Ilham Wardhana, Muhammad Ichwan Musa (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
The purpose of this study aims to determine the effect of online customer reviews on customer trust in e-commerce shopee among students of the Faculty of Economics and Business, Makassar State University. The population in this study is the undergraduate business economics students at Makassar State University as consumers who have made purchases on the Shopee site with a population of 5445 Makassar State University students. The minimum sample for this research is 98 respondents from the Faculty of Economics. Business Strata (S1) Makassar State University. Overall, this study shows that the respondents' assessment of this research variable, namely Online Customer Review (X), is generally good. This is indicated by the many agreed responses from the independent variable customer trust in the shopee application. Based on the results of this study, it can be concluded that online customer reviews have a positive effect on customer trust in 98 respondents to students of the Faculty of Economics and Business, Makassar State University